Improving students' understanding of plane geometry concepts through simple concrete media among fifth-grade students at sdn 3 balai karangan - Wahid Surono; Vikram Yuda Octa Firandhi; Sri Minarti (JURNAL PENDIDIKAN DASAR, 2026)
This study aimed to determine the effect of simple concrete media on fifth-grade students' conceptual understanding of plane geometry. The study was motivated by students' low understanding of area and perimeter concepts, as they tended to memorize formulas without understanding their meanings. This research employed a quantitative approach with an experimental method and a one-group pre-test-post-test design. The sample consisted of 22 fifth-grade students from Class VB at SDN 3 Balai Karangan, selected using purposive sampling Data were collected through pre-test and post-test instruments and analyzed using descriptive statistics, the Shapiro-Wilk normality test, the Paired Samples t-Test, and N-Gain analysis. The results showed an increase in the mean score from 62.73 in the pre-test to 72.05 in the post-test, with a significance value of 0.000 (p < 0.05). However, the average N-Gain score was 0.2774, which falls into the low category. Thus, the use of simple concrete media had a positive and statistically significant effect on students' conceptual understanding of plane geometry.